Penghambatan Oksidasi LDL oleh Ekstrak Air Jahe (Zingiber officinale Roscoe) Secara In Vitro - Aisyah Tri Septiana; Fransiska Rungkat Zakaria (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
Oxidative modification of LDL is believed to play an important role in atherogenesis. Water extract of ginger rhizomes exhibited antioxidative activity is higher than α tocopherol using linoleic acid as substrate. In addition, these extract is kind of ginger extract that daily consumed so may be can be used as functional food. We investigated the effect of in vitro these extract enrichment of LDL on the prevention of oxidative LDL by CuSO4. Plasma was supplemented with 430 or 4300 µg/ml water extract in dimethylsulfoxide (DMSO) (10 µ DMSO per ml plasma), incubated, and the LDL was isolated. Ginger extract also was suplemented on LDL was isolate, and incubated. Lag phase and malonaldehide content was analized after the isolated LDL was oxidized using CuSO4. The result showed that water extract of ginger rhizomes suplementation reduced melonaldehide formation depended on its suplementation. Suplementation these extract on plasma (4300 µg/ml plasma) only reduced 19,04 % malonaldehide content, whereas α tocopherol suplemtation can reduced 26,29 % malonaldehide formation. These extract suplementation on LDL isolate can reduced 43,91 % malonaldehide formation. This research has shown that ginger extract is capable of protecting LDL from oxidation.